Trends and prospects of Lithuania's trade in agricultural and food products with BRICs - Andrej Bogdanov; Tamara Petuchova (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
This study explores trends and perspectives of Lithuania's trade in agricultural and food products with the BRIC countries. Agriculture is one of the priority sectors of Lithuania's economy and plays an important economic and social role. The share of agricultural and food products within the overall foreign trade of Lithuania is significant, and exports to the BRIC countries account for nearly one third of the Lithuanian agricultural and food products exports. BRICs economic development and growing population leads to the increasing food consumption. The potential of these markets is attractive for Lithuania's foreign trade. Therefore, consideration of trade flow in food and agricultural products between Lithuania and the BRIC countries is currently very topical. The econometric forecasting model of Lithuania's Export and Import flows, created by the authors, was applied to predict trade with the BRIC countries in the medium-term period. The authors analyzed the structure of Lithuania's trade in agricultural and food products with the specific BRIC countries, estimated influence of external and internal factors changes.
Keywords: F17; F47; 330; foreign trade in agricultural and food products; econometric model; forecast; Lithuania; BRIC